The student's anatomy of exercise manual 2026-02-16T09:31:34+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Ashwell, Ken W. S. (Barron's Educational Series, Inc., 2012)

(untitled)
This manual clearly explains how to execute fifty essential exercises properly, providing tips aimed at different fitness levels. Includes warning to help you avoid injury, and help you improve the effectiveness of our workout and rehabilitation routines